(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
This paper presents numerical scheme for solving singular Volterra integral equations via midpoint rule. The functions were approximated under the integrals by considering the non-variable subinterval. The convergence analysis of the error bound of the scheme is established. The numerical results show that the scheme has less number of iterations to obtain the best errors compared with other method